Generalized compactness in fuzzy bitopological spaces - Alharbi, Ahlam Ahmed; Kilicman, Adem (New York Business Global, 2024)
The main objective of this research is to study some types of generalized closed sets in fuzzy bitopology including (i, j)-gα-cld, (i, j)-gs-cld, (i, j)-gp-cld, and (i, j)-gβ-cld. We then present basic theorems for determining their relationships and explain their properties, such as closure and interior. In addition, there are many interesting counterexamples. The last part of the research focuses on compactness as an application of the types of fuzzy generalized closed sets in fuzzy bitopological spaces and their types and explores the relationships between these concepts, their important theories, and some relevant counterexamples. This approach provides a better characterization of fuzzy compactness and allows for more precise characterization in fuzzy bitopology. The results of this study are new to the domain of fuzzy bitopology.